^<40>Ar-^<39>Ar Age Studies for Tectonics of the Gondwana Land - Takigami Yutaka; Sugiura Naoji (Tohoku University, 1997)
^<40>Ar-^<39>Ar age studies have been performed for samples from Antarctica and India which were parts of the Gondwana land at Mesozoic and Paleozoic time in order to investigate their thermal history and tectonic movement. From the both areas, ages of about 500 Ma which have been considered to be the age of Pan-African Orogeny were obtained, which represents that this thermal event spread widely over the Gondwana land.